2009
DOI: 10.1021/ol9005757
|View full text |Cite
|
Sign up to set email alerts
|

Simple One-pot Conversion of Aldehydes and Ketones to Enals

Abstract: A simple and efficient method to convert aldehydes into α,β-unsaturated aldehydes with a two-carbon homologation is presented. Hydroboration of ethoxy acetylene with BH 3 •SMe 2 generates tris (ethoxyvinyl) borane. Transmetallation with diethylzinc, addition to aldehydes or ketones, and acidic workup affords enals. When the addition is quenched with anilinium hydrochloride, 1,2-dithioglycol, or acetic anhydride the unsaturated imine, dithiolane, or 1,1-diacetate is isolated in high yield. These transformations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…We,1519 and others,20–29 have used this method to make allylic alcohols, and we have applied it to the synthesis of α- and β-amino acid derivatives,61, 62 epoxy alcohols,16, 17, 63 and cyclopropyl and vinyl cyclopropyl alcohols 19, 64, 65. This method works well with terminal and internal alkynes and we have shown that ethoxy ethynyl ether can also be employed 18, 66. It was not clear at the outset whether the uncatalyzed hydroboration of internal ynamides would proceed with high regioselectivity.…”
Section: Resultsmentioning
confidence: 92%
“…We,1519 and others,20–29 have used this method to make allylic alcohols, and we have applied it to the synthesis of α- and β-amino acid derivatives,61, 62 epoxy alcohols,16, 17, 63 and cyclopropyl and vinyl cyclopropyl alcohols 19, 64, 65. This method works well with terminal and internal alkynes and we have shown that ethoxy ethynyl ether can also be employed 18, 66. It was not clear at the outset whether the uncatalyzed hydroboration of internal ynamides would proceed with high regioselectivity.…”
Section: Resultsmentioning
confidence: 92%
“…Of the many nonbasic nucleophiles we surveyed [including vinyl zinc (36) and cerium (37) reagents], only vinyl zincate 16 cleanly engaged the C17 aldehyde to afford aldehyde 18 (78% yield) after in situ hydrolysis. Subsequently, the C25/C26 acetonide and C19 ketal groups were removed and the C26 alcohol protected to afford aldehyde 2 .…”
mentioning
confidence: 99%
“…The use of isolated ketenes and α-aryloxy aldehydes adds several steps to the preparation of the starting materials. We therefore sought to use α,β-unsaturated aldehydes as substrates, as these compounds are widely employed in a variety of enantioselective organocatalytic reactions and they are increasingly commercially available or readily prepared by improved methods (30). Although this has proven possible in carefully designed intramolecular systems, such as those reported by Scheidt and co-workers (31), the use of simple α,β-unsaturated aldehydes as ester enolate precursors has not been achieved.…”
mentioning
confidence: 99%